Using Tongue Twister to Improve Studentsâ€™ Pronunciation - Lutfiani, Dewi (Universitas Muhammadiyah Jember, 2017)
peaking skill comprises five components; pronunciation, vocabulary, grammar,fluency and accuracy, which are very essential in delivering messages orinformation clearly. As one of the five components of speaking, pronunciationis an essential component in oral communication and a basic ability of speakingEnglish. Since English is a foreign language, correct pronunciation becomesa crucial matter to avoid misunderstanding between a speaker and a listener.Therefore, teaching pronunciation to EFL students is very essential, and it is notan easy task for English teachers. The main reason is that English pronunciationis difficult for most foreign language learners since what is written is differentfrom what is spoken. Regarding the difficulty of the students, teachers shouldbe creative to select a technique of teaching pronunciation. One techniquethat is suitable for teaching pronunciation is tongue twister. This techniquewas applied to the eleventh grade of SMA Muhammadiyah 3 Jember in the2015/2016 academic year. The results of the classroom action research whichwas done in two cycles showed 77.14% students got score â‰¥75 and 77.13% ofthe students were active in teaching learning process. The results had met thecriteria of success of the research.